2008
DOI: 10.1038/nature07154
|View full text |Cite
|
Sign up to set email alerts
|

Compositional differences between meteorites and near-Earth asteroids

Abstract: Understanding the nature and origin of the asteroid population in Earth's vicinity (near-Earth asteroids, and its subset of potentially hazardous asteroids) is a matter of both scientific interest and practical importance. It is generally expected that the compositions of the asteroids that are most likely to hit Earth should reflect those of the most common meteorites. Here we report that most near-Earth asteroids (including the potentially hazardous subset) have spectral properties quantitatively similar to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
146
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(158 citation statements)
references
References 21 publications
10
146
1
1
Order By: Relevance
“…Thus, establishing links between the spectral properties of NEAs and those measured in the laboratory for meteorite samples is fundamental to determine their possible parent bodies (Burbine et al, 2002;Binzel et al, 2002). Recent studies show that about 2/3 of the observed NEAs have surface compositions consistent with LL chondrites, which represent only about 10% of the ordinary chondrites falls (Vernazza et al, 2008;de León et al, 2010;Dunn et al, 2013). These results contradict the general assumption that the spectral characteristics of the most common type of NEAs should be consistent with those of the most common meteorites to fall on Earth.…”
Section: Introductioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Thus, establishing links between the spectral properties of NEAs and those measured in the laboratory for meteorite samples is fundamental to determine their possible parent bodies (Burbine et al, 2002;Binzel et al, 2002). Recent studies show that about 2/3 of the observed NEAs have surface compositions consistent with LL chondrites, which represent only about 10% of the ordinary chondrites falls (Vernazza et al, 2008;de León et al, 2010;Dunn et al, 2013). These results contradict the general assumption that the spectral characteristics of the most common type of NEAs should be consistent with those of the most common meteorites to fall on Earth.…”
Section: Introductioncontrasting
confidence: 55%
“…This degree of thermal metamorphism indicates that the parent body where Itokawa originated must have had a diameter larger than 20 km, necessary to reach temperatures of ∼ 800 o C that can explain the range of petrologic types observed among the Itokawa particles . LL ordinary chondrites have been linked to the Flora family (Vernazza et al, 2008), which is located in the inner part of the main belt near the ν 6 secular resonance. Although the derived silicate compositions of 241662 (2000 KO44) and19764 (2000 NF5) are consistent with that of LL ordinary chondrites, we noticed that their olivine abundances (66%) are lower than the ranges found by Vernazza et al (2008) for LL chondrites (70-85%), and members of the Flora family (76-82%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments in the laboratory with meteorite samples found that reflectance spectra are darker and bluer for coarser grain sizes, supporting their hypothesis. Vernazza et al (2008) made a histogram of the ol ol+px ratios of 57 ordinary chondrites. This histogram has a peak around 0.65 which corresponds to OC-L meteorites that are in contrast with a similar histogram of 38 NEAs belonging to the S-complex, which has a peak around 0.8.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the position of the 1 and 2a µm bands and on the band area ratio, and using calibrations derived from laboratory measurements of meteorites, the authors conclude that 25% of their sample were compatible with the OC mineralogy. Vernazza et al (2007) use a sample of 150 spectra of S-complex asteroids from 0.4 to 2.5 µm (but with the visible and NIR portions obtained at different occasions) to investigate this issue. The authors use Shkuratov et al (1999) radiative transfer model, the Brunetto et al (2006) space weathering model, and optical constants derived from the work of Lucey (1998) in their analysis.…”
Section: Discussionmentioning
confidence: 99%